Simultaneous changes in the function and expression of beta 1 integrins during the growth arrest of poorly differentiated colorectal cells (LISP-1) - Roela,R.A. (2003)
Cells usually lose adhesion and increase proliferation and migration during malignant transformation. Here, we studied how proliferation can affect the other two characteristics, which ultimately lead to invasion and metastasis. We determined the expression of ß1 integrins, as well as adhesion and migration towards laminin-1, fibronectin, collagens type I and type IV presented by LISP-1 colorectal cancer cells exposed to 2.5% dimethyl sulfoxide (DMSO), an agent capable of decreasing proliferation in this poorly differentiated colorectal cell line. Untreated cells (control), as shown by flow cytometry and monoclonal antibodies, expressed alpha2 (63.8 ± 11.3% positive cells), alpha3 (93.3 ± 7.0%), alpha5 (50.4 ± 12.0%) and alpha6 (34.1 ± 4.9%) integrins but not alpha1, alpha4, alphav or ß4. Cells adhered well to laminin-1 (73.4 ± 6.0%) and fibronectin (40.0 ± 2.0%) substrates but very little to collagens. By using blocking monoclonal antibodies, we showed that alpha2, alpha3 and alpha6 mediated laminin-1 adhesion, but neither alpha3 nor alpha5 contributed to fibronectin adherence. DMSO arrested cells at G0/G1 (control: 55.0 ± 2.4% vs DMSO: 70.7 ± 2.5%) while simultaneously reducing alpha5 (24.2 ± 19%) and alpha6 (14.3 ± 10.8%) expression as well as c-myc mRNA (7-fold), the latter shown by Northern blotting. Although the adhesion rate did not change after exposure to DMSO, alpha3 and alpha5 played a major role in laminin-1 and fibronectin adhesion, respectively. Migration towards laminin-1, which was clearly increased upon exposure to DMSO (control: 6 ± 2 cells vs DMSO: 64 ± 6 cells), was blocked by an antibody against alpha6. We conclude that the effects of DMSO on LISP-1 proliferation were accompanied by concurrent changes in the expression and function of integrins, consequently modulating adhesion/migration, and revealing a complex interplay between function/expression and the proliferative state of cells.